Antibacterial Potential of the Methanol Stem Bark Extract of Stachytarpheta Indica - Akuodor, Christian Godwin; Udia, Monday Pius; Udenze, Charles Emeka; Ogbonna, John Onyemaechi (Asian Journal of Medical Sciences, 2013)
<!--[if gte mso 9]> <![endif]--> Objective: There is increasing need for potent antimicrobial agents to tackle the problem of diseases in man. In view of this, the activities of methanol stem bark extract of Stachytarpheta indica was evaluated against some disease causing microorganisms. Method: The activity of the extract against S. aureus, P.aeruginosa, E. coli, S. typhi and Shigella spp was determined using agar diffusion technique. Results: The methanol stem bark extract demonstrated significant activity against the test organisms. The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of the stem bark extract ranged from 12-60 μg/ml. Conclusion: Further isolation of active compound responsible for the antibacterial activity could be the potential sources of new antibacterial agents. Asian Journal of Medical Science, Volume-4 (2013), Pages 5-10 DOI: http://dx.doi.org/10.3126/ajms.v4i4.8248 <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] -->